Narratological Analysis of Poetry: An Introduction (KULT_online, 2009)
The study Lyrik und Narratologie (Poetry and Narratology) emerged from the DFG research group on narratology based in Hamburg and working from 2001 to 2004. The three authors provide exemplary analyses of twenty lyrical texts, taken from German poetry of the 16th to the 20th century, with a main focus on texts from the 19th century to the present. The essays develop a narratological method of analysis and thus seek to expand the methodology of the study of poetry.